Large Dams and Welfare : Empirical Study in Indonesia - Gunawan Aribowo; Muhammad Halley Yudhistira (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
In addition to solving the problem of water shortage for irrigation, energy and consumption, thepolicy of building large dam is also expected to improve population-welfare. However, previousstudies suggest that people living near dams have less benefit from the existence of large dam. Thisstudy aims to provide empirical evidence the effect of large dam development on welfare tohousehold living in sub-districts around large dam placement using National Socio-EconomicSurvey (SUSENAS) data in 2013-2018 from Central Bureau of Statistics and spatial large dam datain Indonesia. Estimated results indicate that addition large dam tend to be negatively correlated by2.4-3.1 % with household consumption implying a tendency of decreasing welfare in localhouseholds. Estimated findings using Indonesia Family Life Survey (IFLS) in 2007 and 2014 shownegative correlation likely to be caused by lower agricultural productivity and work activity. Thisresult show there are economic agents who suffer from large water - infrastructure especiallyhouseholds living in sub-districts close to the dam.